Number theory and algebraic geometry : (Cambridge University Press, 2003)
Peter Swinnerton-Dyer's mathematical career encompasses more than 60 years' work of amazing creativity. This volume, dedicated to him on the occasion of his 75th birthday, provides contemporary insight into several subjects in which his influence has been notable. The contributions come from leading researchers in analytic and arithmetic number theory, and algebraic geometry. Topics treated include rational points on algebraic varieties, the Hasse principle, Shafarevich-Tate groups of elliptic curves and motives, Zagier's conjectures, descent and zero-cycles, Diophantine approximation, and Abelian and Fano varieties.